Apuntes en torno al simbolismo de la arquitectura cupulada bizantina - Marín Riveros, José (Byzantion Nea Hellás, 2015)
In this work, the author analyzes the Christian symbolism of the Byzantine architecture, especially the case of the Church of Edessa, through the Hymn of the dedication of the Temple. There is a close relation between the religious construction and the cosmos, i.e., the Church is built as an imago mundi. The author analyzes, first, the form of the Church, and later his symbolic meaning, highlighting the importance of the interior Light, image of the Divine Light. This symbolism had a wide diffusion in the Byzantine times.